Performance Evaluation of Stocks’ Valuation Models at MSE - Ivanovski Zoran; Narasanov Zoran; Ivanovska Nadica (Studia Ekonomiczne i Regionalne, 2018)
Subject and purpose of work: The main task of this paper is to examine the proximity of valuations generated by different valuation models to stock prices in order to investigate their reliability at Macedonian Stock Exchange (MSE) and to present alternative “scenario” methodology for discounted free cash flow to firm valuation. Materials and methods: By using publicly available data from MSE we are calculating stock prices with three stock valuation models: Discounted Free Cash Flow, Dividend Discount and Relative Valuation. Results: The evaluation of performance of three stock valuation models at the MSE identified that model of Price Multiplies (P/E and other profitability ratios) offer reliable stock values determination and lower level of price errors compared with the average stocks market prices. Conclusions: The Discounted Free Cash Flow (DCF) model provides values close to average market prices, while Dividend Discount (DDM) valuation model generally mispriced stocks at MSE. We suggest the use of DCF model combined with relative valuation models for accurate stocks’ values calculation at MSE.